ERGODYNAMICS AND A SEMIOTICS OF INSTRUMENTAL COMPOSITION. (24th December 2018) - Magnusson, Thor
Abstract: This article examines the techno-philosophical aspects of how we create and understand musical systems in twenty-first century computational media. Arguing that processor-based media have exploded the compositional language of new music, the article proposes a set of concepts that might help us navigate this new space of instrumental possibilities. The term 'ergodynamics' – and related concepts – is proposed as a useful concept when describing the phenomenological, historical and aesthetic aspects of musical instruments, as well as a lens for looking at new compositional practices that can be defined as being either 'idiomatic' or 'supra-instrumental'. The article explores the difference in composing for acoustic, electronic and digital instruments, and suggests that new musical practice can be characterised by a move from composing work to inventing systems.